Critical Inversion - François Cusset (Media Theory)
Today’s intellectual and ideological conjuncture is marked not so much by a demise of critical labor, but by a confiscation of critical grammars and gestures by the very enemies of the progressive forces historically associated with the modern rise of critique: ultraconservatives and neofascists who are taking advantage of the crisis of intellectual institutions, the failure of social-democratic politics, and the affordances of fast-rising digital media, to disconnect social critique from its traditional progressive politics and thus appear like the new bearers of cognitive freedom and critical audacity. This paper maps the various factors and contexts making such a critical inversion a clear and present danger today.